Green nudges: Do they work? Are they ethical? - Christian Schubert (Philipps-University Marburg, School of Business and Economics, 2016)
Environmental policies are increasingly informed by behavioral economics insights. 'Green nudges' in particular have been suggested as a promising new tool to encourage consumers to act in an environmentally responsible way, such as choosing renewable energy sources or saving energy. While there is an emerging literature on the instrumental effectiveness of behavioral policy tools such as these, their ethical assessment has largely been neglected. This paper attempts to fill this gap by, first, providing a structured overview of the most important contributions to the literature on pro-environmental nudges and, second, offering some critical guidelines that may help the practitioner come to an ethically informed assessment of nudges.
Keywords: 330; Nudges; Libertarian Paternalism; Behavioral Economics; Green Defaults; Autonomy